Identifikasi Endoparasit Pada Ikan Gabus ( Channa striata ) di Sungai Sebangau Palangka Raya Kalimantan Tengah - Maryani Maryani; Shinta Sylvia Monalisa; Ide Refika BR Sembiring; Toto Fransisco (Jurnal Akuakultur Sungai dan Danau, 2022)
The study aimed at identifying  of endoparasites that infect snakehead (Channa striata) fish as well as to determine the prevalence of the endoparasite species in snakehead fish then examined at Parasitology Laboratory of Fish Quarantine Station Quality Control and Safety of Fishery Products in Palangka Raya. Examination of endoparasites is done by observing the internal organs and by making a mucus smear which is examined under a microscope. From the results of the study found 2 types of parasites that infest snakehead fish in the Sebangau River, Palangka Raya, namely Procamallus sp dan Camallanus sp. The most common endoparasites that attack the gills of snakehead fish are Camallanus sp with a prevalence of 20% and an intensity of 3 cells/ind,  and Procamallus sp with a prevalence of 10% and an intensity of 2 cell/ind.